OPTIMIZING BOYLE'S LAW PRACTICUM USING A PHET-BASED VIRTUAL HOT LAB - Salsabila, Luthfiah Dewi; Malik, Adam (Science Education, Institut Agama Islam Negeri Ponorogo, 2025)
This research emphasizes the urgency of using PhET-based virtual laboratories in Boyle’s Law experiments to enhance students’ understanding of gas properties, specifically the relationship between pressure and volume at constant temperature. By applying an inquiry-based HOT Lab approach, students can actively manipulate gas variables and observe real-time pressure changes through the simulation. The findings indicate that the PhET simulation significantly aids students in grasping Boyle’s Law principles by providing an interactive and engaging learning experience. Furthermore, this approach supports the development of critical and analytical thinking skills and accommodates various learning styles and paces, making it an inclusive educational tool. Given the challenges in physics learning, especially in the context of online education, integrating virtual simulations with physical laboratory activities in the future could enrich the learning experience and deepen students’ understanding of fundamental physics concepts.